Mass Transfer in Eccentric Black Hole–Neutron Star Mergers - Yossef Zenati; Mor Rozner; Julian H. Krolik; Elias R. Most (The Astrophysical Journal)
Black hole–neutron star binaries are of interest in many ways: they are intrinsically transient, radiate gravitational waves detectable by LIGO, and may produce γ -ray bursts. Although it has long been assumed that their late-stage orbital evolution is driven entirely by gravitational wave emission, we show here that in certain circumstances, mass transfer from the neutron star onto the black hole can both alter the binary's orbital evolution and significantly reduce the neutron star's mass: when the fraction of its mass transferred per orbit is ≳10 ^−2 , the neutron star's mass diminishes by order unity, leading to mergers in which the neutron star mass is exceptionally small. The mass transfer creates a gas disk around the black hole before merger that can be comparable in mass to the debris remaining after merger, i.e., ~0.1 M _⊙ . These processes are most important when the initial neutron star–black hole mass ratio q is in the range ≈0.2–0.8, the orbital semimajor axis is 40 ≲  a _0 / r _g  ≲ 300 ( r _g  ≡  GM _BH / c ^2 ), and the eccentricity is large at e _0  ≳ 0.8. Systems of this sort may be generated through the dynamical evolution of a triple system, as well as by other means.